Permainan Tradisional Estafet Sarung untuk Meningkatkan Motivasi Belajar Anak (Studi di Desa Giripawana, Mandalawangi, Pandeglang) - Zahrotul Faridah; Anisa Dewi; Ahmad Sudrajat; Naf’an Tarihoran (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
The sarong relay game is a traditional group game by moving the sarongs while holding hands without being missed. The main goal of the sarong relay game is to reach the finish line faster than the opposing team by running a series of tasks that involve the use of sarongs. The researcher used a qualitative method with an observation method or direct interviews with respondents. This research was carried out in conjunction with the 79th independence of the Republic of Indonesia, on August 17, 2024 in Giripawana Village in the implementation of the sarong relay game competition. The results obtained from this study were that from 25 respondents the children felt happy and entertained and motivated to learn to work together, concentrate, never give up and compete healthily to become champions.